Magnesium layered double hydroxide nanofiller in PMMA exposed to gamma irradiation - Dandara Luz Souza de Oliveira; Amanda Damasceno Leão; Fábio de Oliveira da Silva Ribeiro; Alyne Rodrigues de Araújo; Pietro Paolo Jorge Correia de Oliveira e Silva; José Lamartine Soares-Sobrinho; Elmo Silvano de Araújo; Renata Francisca da Silva Santos; Kátia Aparecida da Silva Aquino (Polímeros)
Abstract Poly(methyl methacrylate) (PMMA) is a polymer that can be used in applications requiring its exposition to gamma radiation, nevertheless, the radiation induces main chain scission backbone, leading to modification in some properties. Therefore, using materials such as layered double hydroxide (LDH), was evaluated as a new radiation shielding agent. This work synthesized LDH and added to PMMA by an in-situ polymerization method. Viscosimetric analysis showed that LDH at 0.25 wt% concentration promotes polymer radiolytic protection of 90% against damage caused by gamma radiation. The topographic images obtained by AFM revealed increasing PMMA/LDH film roughness, which impacted the lower film transmittance. The combined effect of LDH and gamma radiation interferes with the degradation process of PMMA, promoting reduced rigidity, greater mobility of polymer chains, and lower optical gap energy. Thus, these results open a promising path for using LDH as additives in polymers exposed to gamma radiation.